In vitro Efficacy of the Antifungal Activity of Some Thai Medicinal-Plants on the Pathogenic Fungus, Saprolegnia parasitica H2, from Fish - Pareeya Udomkusonsri; Kamolchai Trongvanichnam; Malinee Limpoka; Narumol Klangkaew; Napasorn Kusucharit (Agriculture and Natural Resources, 2007)
Ethanol crude extracts of galanga (Alpinia galanga) (rhizome), betel vine (Piper betel Linn.) (leaves), Rhinacanthus nasutus Linn. (leaves), Kaempferia galanga Linn. (leaves and roots) were studied for fungistatic and fungicidal activity against water mold Saprolignea parasitica H2. Minimal inhibitory concentration (MIC) of crude extracts of betel vine leaves and K. galanga Linn. roots against S. parasitica H2 were 500 and 125 μg/ml, respectively. The crude of R. nasutus Linn. leaves at 500 μg/ml could inhibit fungal growth for 46%. The crude extracts of galanga rhizome and K. galanga leaves at 500 μg/ml had minimal fungistatic activity against S. parasitica H2. The fungicidal concentrations of crude extracts of betel vine leaves, R. nasutus Linn. leaves and K. galanga Linn. leaves against S. parasitica H2 were 500 μg/ml after 24 hr-immersion, 5,000 μg/ml after 24 hr-immersion and 50 μg/ml after 120 min-immersion, respectively. Crude extracts of galanga rhizome and K. galanga Linn. leaves at 5,000 μg/ml had no fungicidal effects in this study. In addition, the fungicidal activity varied between concentration of plant extract and exposure time. This study presented that the crude extracts from betel vine leaves and K. galanga Linn. roots had high antifungal activity against S. parasitica H2, while R. nasutus Linn. leaves had moderate activity.